Challenges Faced by English Student Teachers on Implementing Kurikulum Merdeka During the Teaching Practicum Program - Lisa Kurnia Ningsih; Aryuliva Adnan (Journal of English Language Teaching, 2023)
The purpose of this research is to find out the challenges faced by English student teachers on implementing Kurikulum Merdeka during teaching practicum program. This study used qualitative research using interview methods with 13 student teachers who were in teaching practicum program. The results showed that student teachers who had been interviewed showed clear and convincing evidence about the challenges that they faced on implementing Kurikulum Merdeka during teaching practicum program. According to the student teachers, they faced challenges on implementing Kurikulm Merdeka because Kurikulum Merdeka is new for them. When they learned micro teaching they only focused on the Kurikulum 2013, but it turned out that when they were in the field they had to teach based on the Kurikulum Merdeka. Almost all the respondent faced challenges in implementing Kurikulum Merdeka such as, challenges in designing teaching modules, challenges in class management, challenges in learning projects, and doing assessments based on Kurikulum Merdeka